2002
DOI: 10.1200/jco.2002.20.6.1480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Individuals With Germline Mutations in BRCA1 and BRCA2: Analysis of 10,000 Individuals

Abstract: Specific features of personal and family history can be used to assess the likelihood of identifying a mutation in BRCA1 or BRCA2 in individuals tested in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
226
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(247 citation statements)
references
References 28 publications
14
226
2
5
Order By: Relevance
“…Our numbers are comparable to what others have revealed [43]. Studies have reported that physicians, with limited formal training in genetics, may misinterpret VUS results [44–46].…”
Section: Discussionsupporting
confidence: 88%
“…Our numbers are comparable to what others have revealed [43]. Studies have reported that physicians, with limited formal training in genetics, may misinterpret VUS results [44–46].…”
Section: Discussionsupporting
confidence: 88%
“…The referred criteria for breast cancer were: (1) breast cancer patients with a family history of breast or ovarian cancer; (2) breast cancer patients who were 40 years or younger during diagnosis, who had bilateral breast cancer or breast cancer with other primary malignancy, or male breast cancer patients, in accordance with the standard of National Medical Insurance Reimbursement in Korea. In the genetic counseling process, all patients’ mutation probabilities were estimated by CaGene5.0 software [15] using pedigree information up to second-degree relatives and considering estimates by BRCAPRO [16] and Myriad [17]. Clinicopathological characteristics of cancer, such as the stage and the hormone receptor and human epidermal growth factor receptor 2 (HER2) status, were evaluated by reviewing medical records.…”
Section: Methodsmentioning
confidence: 99%
“…The cancer risk associated with BRCA1 germline mutation is less clear for tumors other than breast, ovary, and fallopian tube cancers (BCLC, 1999;Brose et al, 2002;Thompson and Easton, 2002). Large studies have reported both a lack of association and small association with BRCA1 mutation in male breast and prostate cancer (Basham et al, 2002;Brose et al, 2002;Frank et al, 2002;Thompson and Easton, 2002). A recent editorial commenting on reports from two large and overlapping databases brings to light the difficulties in estimating/establishing other small cancer risks due to BRCA1 mutation (Gruber and Petersen, 2002).…”
Section: Brca1 and Brca2 Tumor Suppressionmentioning
confidence: 99%